Ti-Al-Ta alloy for fuel cell bipolar plates with low contact resistance - SONG Mengfan; WANG Qing; DONG Chuang (Cailiao gongcheng)
Titanium and titanium alloys with surface-prepared coatings have excellent overall performance as bipolar plates for proton exchange membrane fuel cells， but the bare plates will form passivation films with poor electrical conductivity during service， reducing the efficiency of the whole machine. By studying the feasibility of α-corrosion resistant titanium alloy Ti35 （Ti5Ta） and its Al alloying， the electrical conductivity of bare plate was improved on the premise of ensuring corrosion resistance. Using the cluster-type composition design method developed by the group and combing with the highest solid solution degree on the phase diagram， three kinds of Ti-Ta alloys with compositions of Ti-7Ta， Ti-8.3Ta， and Ti-9.6Ta and three kinds of Ti-Al-Ta alloys with compositions of Ti-2.6Al-5.8Ta， Ti-3.8Al-8.6Ta， and Ti-5Al-11.3Ta were designed. The experimental results show that the cathodic current density of the developed alloy is lower than that of the reference alloy TC4 under the simulated cathodic service environment （0.5 mol/L H2SO4+2×10-6 HF） at a constant potential polarization voltage of 0.6 V （vs. SCE） for 4 h. The cathodic current density of the designed alloy is lower than that of the reference alloy TC4， among which the Ti-8.3Ta alloy has the smallest value of 0.72 μA·cm-2. Under 1.5 MPa loading pressure， with the increase of Ta content， the interfacial contact resistance （ICR） value gradually decreases and is better than that of the pure titanium and TC4. The ICR value of Ti-5Al-11.3Ta alloy is the smallest， which is 18.3 mΩ∙cm-2， and its cathodic polarization current density is 0.91 μA·cm-2. In summary， the appropriate addition of Ta and Al can effectively improve the service performance of titanium alloy bipolar plates， and it is expected to realize the preparation of titanium alloy bipolar plate materials without coating.